Cats at the campground - Baglio, Ben M.; Baum, Ann (New York : Scholastic, 2001)
Mandy and James discover a stray cat and her kittens and try to save them.
"An Apple paperback."
4.0.
008-011.
Keywords: Cats -- Juvenile fiction; Animal welfare -- Juvenile fiction; Animal Ark (Imaginary organization) -- Juvenile fiction; Cats -- Fiction